Pengobatan Pasien Gangguan Jiwa yang Dipasung Oleh Keluarga: Studi Kasus di Kabupaten Trenggalek - Sulisetiorini; Adji Prayitno; Yosi Irawati Wibowo (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2024)
Abstract—In Trenggalek Regency, East Java Province, psychotic patients are still found on pasung by their families even though the Free Pasung Program has been intensively carried out since 2015 by The Indonesian Government. This research aims to identifying the characteristics and status of pasung, medication history, and patient’s adherence to medication. The data collection was carried out through interviews with family members of patients with pasung and observation of medical records. A total of 14 psychotic patients were included in this study. Patients were in the productive age of 30-60 years (100%), not working (92.86%), the ratio of patients on pasung and with history of pasung was 1:1, the highest educational level was elementary school (71.43%), and family history (14.29%). Out of 14 patients, 3 patients received no medications, 4 patients received both oral and injectable medications, and 7 patients received oral medications; the majority of patients were given complementary medications (64.29%). The most common injections given were haloperidol decanoate and long-acting flufenazine decanoate; while oral medications frequently given were risperidone, chlorpromazine, trihexiphenidyl, haloperidol and trifluoperazine. Patients’ medication adherence rate was 63,64%. This finding indicated the importance of pharmacists’ role in providing drug information and counseling services to improve medication adherence of patients with psychotics. Keywords: adherence, pasung, pharmacist, psychotic Abstrak—Di Kabupaten Trenggalek Provinsi Jawa Timur masih ditemukan pasien gangguan jiwa psikotik yang dipasung oleh keluarga meskipun Program Bebas Pasung sudah gencar dilakukan sejak tahun 2015 oleh pemerintah Indonesia. Penelitian ini bertujuan untuk mengidentifikasi karakteristik dan status pasung, riwayat pengobatan, serta kepatuhan pasien terhadap pengobatan. Metode pengumpulan data melalui wawancara anggota keluarga pasien dengan pasung dan pengamatan rekam medis. Empat belas pasien gangguan jiwa psikotik terlibat dalam penelitian ini. Pasien berusia produktif 30-60 tahun (100%), tidak bekerja (92,86%), rasio status pasien dalam pasung dan riwayat pasung adalah 1:1, riwayat pendidikan terbanyak adalah sekolah dasar (71,43%), dan riwayat keluarga (14,29%). Dari 14 pasien, 3 pasien tidak menerima pengobatan, 4 pasien menerima pengobatan oral dan suntikan, dan 7 pasien menerima pengobatan oral; mayoritas pasien menerima pengobatan komplementer (64,29%). Obat suntikan yang paling umum diberikan adalah haloperidol dekanoat dan flufenazine dekanoat kerja panjang; sedangkan obat oral yang sering diberikan adalah risperidon, klorpromazin, triheksifenidil, haloperidol dan trifluoperazin. Tingkat kepatuhan pengobatan pasien adalah 63,64%. Temuan ini menunjukkan pentingnya peran apoteker dalam memberikan informasi obat dan layanan konseling untuk meningkatkan kepatuhan pengobatan pasien gangguan jiwa psikotik. Kata kunci: apoteker, kepatuhan, pasung, psikotik